Factors affecting preoperative nutritional status of gastric cancer patients at Vietnam National Cancer Hospital - Nguyen, Van Dang; Nguyen, Hong Luong (Tạp chí Y Dược Huế, 2024)
Objective: Gastric cancer (GC) sometimes presents as asymptomatic or exhibits only nonspecific symptoms in its initial stages, resulting in delayed diagnosis and subsequent starvation. Patients with gastric cancer who had preoperative malnutrition faced a heightened risk of unfavorable clinical outcomes. The nutritional status was affected by various factors, including the disease’s location and stage, as well as gastrointestinal symptoms such diminished food intake, abdominal pain, and vomiting. Materials & Method: Between January and December 2023, the Vietnam National Cancer Hospital performed cross-sectional descriptive research on 88 stomach cancer patients to elucidate their dietary status and associated factors. Results: The preoperative malnutrition rates based on albumin, body mass index (BMI), and scored patient-generated subjective global assessment (PG-SGA) were 34.1%, 29.5%, and 55.7%, respectively. Research has not found a relationship between nutritional status assessed by PG-SGA as well as BMI with factors such as age, gender, clinical symptoms, and disease stage. Conclusion: Prior to surgery, GC patients had a very high risk of malnutrition. Research has not found a relationship between nutritional status assessed by PG-SGA as well as BMI with any factors